Development of water channel system for wave structure interaction - Mohamed, Nor Azizi (Universiti Teknologi Malaysia, 2001)
Physical models or laboratory studies had long been used as one of the techniques for water wave research. The wave generat or plays an important role in generating water waves for such studies. In this project, a wave generation system was designed and constructed to generate waves representing prototype with amplitude up to 1 met re and period in the range of 0.1 second to 15 seconds propagating over a depth of up to 15 metres. The system comprise o f a paddle, a paddle stroke controller, and a mechanical component for converting the rotational motion of the motor into a linear motion of the paddle. Two types of paddle chosen are the piston-type and the flap-type. The mechanical system designed is capable of producing sinusoidal waves. The variable voltage power supply operating within the range of' 1.2 volt to 15 volt is able to control the motor speed, thus determine the frequency of the generated wave. This wave generator system is capable of generating water waves in the frequency range of 0,50 Hertz to 10.00 Hertz with amplitude up to 0.02 metres.